Faktor Prediktor Yang Berpengaruh Terhadap Kejadian Pruritus Vulva Mahasiswi Pada Akper Anging Mammiri Makassar - Musriani, Musriani; Samsualam, Samsualam; Fachrin, Suharni Andi (Window of Health : Jurnal Kesehatan, 2019)
Pruritus vulvae is a disorder characterized by severe itching sensation of the external female genitalia. Research conducted by (Bohl, 2005) in America showed that of 160 respondents 100% never experienced Pruritus vulvae. This research aims to know the factors which affect the Predictor Genesis pruritus vulva on Coed Akper Anging Mammiri Makassar when menstruation. The design of the research used in this research is a survey of the analytic approach of Cross-Sectional Study. Sampling was done by the method of purposive sampling with the total sample as much as 91 people. Data analysis using the method of statistical analysis using computer programs. The results of the research there were obtained the influence of knowledge (p = 0,035), attitude (p = 0,035), action (p = 0,035), the availability of clean water (p = 0,009), the type of panties (p = 0.047), the frequency of dressing change (p = 0.030), and the use of sanitizers (p = 0,033) against the incidence of vulvar pruritus at Coed Mammiri Anging Akper Makassar when menstruation and no hand-washing habits influence with the incidence of vulvar pruritus in teenagers while menstruating (p = 1.000). As for the most influential variable is the availability of clean water. The conclusions of the research show that there is knowledge, attitude, action, the availability of clean water, the type of panties, pads, and change the frequency of the use of a cleaning effect on the incidence of vulvar pruritus. So it is advisable to Sorority to improve his behavior associated with vulvar hygiene especially during menstruation to prevent the occurrence of pruritus vulva.